Prevalence of goitre and urinary iodine status of primary-school children in Lesotho. - Sebotsa, Masekonyela Linono Damane (World Health Organization, 2003)
OBJECTIVE: To estimate the prevalence of goitre, urinary iodine status, coverage of supplementation of iodized oil capsules, and current use of iodized salt in children in Lesotho. METHODS: Cross-sectional study of children from 50 primary schools in Lesotho. Thyroid glands of children aged 8-12 years were measured by palpation and graded according to the WHO, UNICEF, and the International Council for the Control of Iodine Deficiency's (ICCIDD) joint criteria. The use of iodized oil capsules was determined by a structured questionnaire and verified with the children's health booklets. Iodine content of household salt samples was analysed. Casual urine samples were analysed for urinary iodine. FINDINGS: Median urinary iodine concentrations of 26.3 microg/l (range 22.3-47.9 microg/l) indicated moderate iodine deficiency. More children in the mountains than in the lowlands were severely iodine deficient (17.7% vs 1.9%). Adjusted prevalence of goitre (4.9%) increased with age, was higher in girls than boys, and ranged from 2.2% to 8.8% in the different districts; this indicated no public health problem. Overall, 94.4% of salt samples were iodized, and coverage of supplementation with iodized oil capsules was 55.1%. CONCLUSION: Mild-to-moderate iodine deficiency exists in Lesotho. Iodine deficiency was more severe in the mountains than the lowlands and is still a concern for public health. Use of iodized salt coupled with iodized oil supplementation effectively controls iodine deficiency disorders. Effective monitoring programmes would ensure the use of adequately iodized salt throughout Lesotho and serve to evaluate progress towards optimal iodine nutrition. Iodized oil capsule supplementation should continue in the mountains.